Konstruksi Realitas Integritas Komisi Pemberantasan Korupsi (KPK) dalam Pemberitaan Media Online - Rezzi Nanda Barizki; Mayang Riyantie (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2021)
The aim of this research is to know the construction of the reality of the reporting on the integrity of the KPK from the framing of online media Kompas.com and Detik.com. The paradigm used is constructivist, with the Entman’s framing analysis method, which means that it is preceded by the assumption that reality tends to have multiple faces (multiple reality). Therefore, this research will have a theoretical contribution to the public's understanding about the construction of mass media reality, and public awareness that the aspects of corruption prevention must be started by the actors of KPK itself (the issue of integrity), as well as for strengthening the anti-graft institution. The results showed that the reality construction formed by excellent reputation media such as Kompas.com and Detik.com will gain high public trust, especially in disclosing information on important state institutions, such as KPK. The similarity construction is related to the public criticism and demand about the existence of KPK as Supervisory Board; on the contrary, it oftentimes still stained by the violation allegation of the ethical code of its leaders. Moreover, there was internal conflict, decreased performance and public pessimism. As for the difference, Kompas.com built a positive image by the KPK's actions in overseeing state institutions and investigating several cases, while Detik.com delivered content on sympathetic social action, coordination with regional leaders, appreciation for the existence of KPK by a popular state figure.